Interdependence, participation, and coordination in the budgeting process - Katrin Weiskirchner-Merten (Business Research, 2020)
This article studies the role of participation in the budgeting process when the company has to coordinate two interdependent divisions. The focus lies on the design of the budgeting process (top-down vs. participative budgets) and the underlying supply of information. This is studied in a principal agent model where two divisions (agents) jointly generate earnings. With the participative budgeting process, the company (principal) implements an information system that provides the division managers with private information. Two economic effects occur. First, the company can benefit from the division managers' private information by perfectly coordinating the divisions' operations. Second, the company has to induce the managers to provide productive effort and with participation, to additionally report truthfully. Thus, the company incurs incentive costs. The two considered budgeting processes trade off these effects diametrically. For a low importance of coordination, the company prefers the top-down budgeting process and not installing an information system that allows the managers to obtain private information. Otherwise, the participative budgeting process is used. In contrast to the company, managers always prefer the participative budgeting process. In addition, the model predicts that a higher earnings potential increases the attractiveness of participative budgets.
Keywords: 650; Interdependence; Coordination; Budgeting process; Participation